The transmission of unconventional monetary policy to bank credit supply: Evidence from the TLTRO - Afonso, António (2020)
We assess the transmission of the Targeted Longer-Term Refinancing Operations (TLTRO) to the bank credit supply for the Euro area (2014–2017) and for Portugal (2011:02– 2018:01), using a panel data setup. In order to estimate a causal effect, we construct an instrumental variable (IV) using the maximum borrowing allowance in the TLTRO. For the Euro area, we find a positive impact of the TLTRO on the amount of credit granted to the real economy, in particular in the less vulnerable countries. For Portugal, using a difference-in-differences model, we find that bidding banks set lower interest rates in relation to non-bidding banks and the difference seems to be larger in 2016 and 2017.